A Comment on "Jobs and Political Participation: Evidence from a Field Experiment in Ethiopia" by Aalen et al. - Mofei Jia; Orestis Kopsacheilis; Essi Kujansuu; Anna Popova (Institute for Replication (I4R), 2025)
Aalen et al. (2024) examine the effect of employment on political participation among women job applicants living with a partner in Ethiopia, using 'intention to treat'-estimates and data from a randomized control trial in the field. In the first stage, the authors find that job offers increased formal employment and earnings. They find no significant effects of job offers on political interest, raising issues, or protest activity but they find negative effects on participation in community meetings, and on internal and external political efficacy. We successfully computationally reproduce the main claims of the paper. Because the data provided is quite limited in its scope, we do only three robustness checks, nevertheless, no large issues come up in the robustness checks.
Keywords: 330